2012
DOI: 10.1108/02756661211242690
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability leadership: from strategy to results

Abstract: PurposeThe purpose of this article is to show how a previously developed multi‐level model of employee engagement can be leveraged to implement a comprehensive sustainability strategy. By combining macro‐level (organization‐wide) with micro‐level (manager to employee) leadership practices, management teams can more effectively engage their entire workforce in sustainability endeavors.Design/methodology/approachA narrative synthesis approach is used to integrate extant empirical and practitioner literature span… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(106 citation statements)
references
References 27 publications
1
96
0
9
Order By: Relevance
“…al., 2016;ALLIO, 2012) e a relacional (BURNS; VAUGHT; BAUMAN, 2015;UHL-BIEN, 2006), assim como engloba o desenvolvimento de novos conceitos e abordagens de liderança, tanto em relação às características, comportamentos e ações do líder quanto das organizações, voltadas à sustentabilidade (SANT'ANNA; NELSON; CARVALHO NETO, 2015b;TIDE-MAN;ARTS;ZANDEE, 2013;GALPIN;WHITTINGTON, 2012;HARDMAN, 2010;ULRICH;SMALLWOOD, 2013).…”
Section: Ferdig (2007) Destaca a Emergência De Novas Visões De Lideraunclassified
“…al., 2016;ALLIO, 2012) e a relacional (BURNS; VAUGHT; BAUMAN, 2015;UHL-BIEN, 2006), assim como engloba o desenvolvimento de novos conceitos e abordagens de liderança, tanto em relação às características, comportamentos e ações do líder quanto das organizações, voltadas à sustentabilidade (SANT'ANNA; NELSON; CARVALHO NETO, 2015b;TIDE-MAN;ARTS;ZANDEE, 2013;GALPIN;WHITTINGTON, 2012;HARDMAN, 2010;ULRICH;SMALLWOOD, 2013).…”
Section: Ferdig (2007) Destaca a Emergência De Novas Visões De Lideraunclassified
“…Na década seguinte, as estratégias ambientais foram ganhando espaço com a discussão sobre eco e socioeficiência e equidade ecológica (Dyllick;Hockerts, 2002), oferecendo orientação aos executivos e estrategistas de negócios (Olson, 2009). Mais recentemente, estudos de caso sobre estratégias ambientais começaram a ganhar destaque em publicações como o Journal of Business strategy (Bonn;Fisher, 2011), assim como novos modelos para o desenvolvimento de estraté-gias ambientais de amplo alcance (Galpin;Whittington, 2012). Publicações mais específicas, como o periódico científico Business strategy and the environment, passaram a divulgar surveys com empresas (Ormazabal;Sarriegi, 2014) ou respostas estratégicas às mudanças climáticas (Galbreath, 2014).…”
Section: Revisão Da Literaturaunclassified
“…Desde 2011, entretanto, verifica-se uma tendência de redução na recomposição do nível do sistema, representada pela reta AB na Figura 8. Essa tendência é reforçada pela Figura 9, que evidencia que ao longo do segundo semestre de 2013 não houve indício de que haveria uma elevação do nível d'água no sistema, informação essa que poderia ter sido utilizada para a concepção de estratégias preventivas (Galbreath, 2014;Galpin;Whittington, 2012). Para melhor avaliar a influência climática, foram utilizados dados primários coletados pela Estação Meteorológica do Instituto Astronômico e Geofísico da Universidade de São Paulo (IAG/USP) e dados secundários fornecidos pelo Climate Prediction Center da National Oceanic and Atmospheric Administration (CPC/NOAA) para a elaboração da Tabela 3.…”
Section: Iag-usp (2014)unclassified
“…Despite this there is in fact little specifically focussed research on the intersection of sustainability and leadership (Brown, 2011;Galpin & Whittington, 2012;Velsor, 2009). In fact the search for an overarching definition as to what constitutes 'leadership' continues, however many agree that leadership is a practical skill that regards the ability of an individual to lead or guide other individuals, teams or entire organisations in the pursuit of an specific endeavor.…”
Section: Leadership For Sustainabilitymentioning
confidence: 99%
“…This is due to the fact that not only do business processes and practices need to change but so too the vision and management approaches that underpin modern organisations. Numerous studies have demonstrated that sustainability actions only take place where there is an active leader and/or manager within a company that champions this approach (Epstein & Buhovac, 2014;Galpin & Whittington, 2012;Székely & Knirsch, 2005). Alongside this business leaders and managers have a central role to play in wellbeing.…”
Section: Introductionmentioning
confidence: 99%